BADANIE STRATEGII UCZENIA SIĘ W JĘZYKU DRUGIM I TRZECIM - Kiermasz, Zuzanna (Neofilolog, 2018)
Although language learning strategies are a well-researched topic, there are still some aspects which need further investigation and one of these is the application of strategic devices in the second and third language. The following article seeks to compare how learners of two foreign languages use strategies and shows both differences and similarities between the application of strategic devices by presenting the results of a research project in which a questionnaire and an interview were used as the research tools. Strategies were found to be used more often when learning the L2 than during the process of learning the L3. Dissimilarities were observed in the specific types of strategies used, especially in the case of metacognitive strategies, while similarities were noted in the use of affective strategies.